Process of Decline in Activities of Daily Living of Older Chinese People Prior to Death: Evidence From Three Cohorts. (September 2019) - Zhang, Wenjuan; Feldman, Marcus W.; Du, Peng
Objective: The study analyzes the decline in activities of daily living (ADL) prior to death among three cohorts of older Chinese. Method: With data from the Chinese Longitudinal Healthy Longevity Survey, the process of decline in ADL in older people born during the periods 1899–1908, 1909–1918, and 1919–1928 is analyzed using the hierarchical linear model with mixed effects. Results: The remaining survival time has a stronger effect on changes in ADL than chronological age, and there is significant heterogeneity among the older adults in ADL. Conclusion: Decline in ADL is delayed by extending life span. Older people with healthy behaviors, good living conditions in childhood, and age-friendly living environment have long-lasting good ADL during their remaining life span; socioeconomic resources help the older adults with ADL disabilities to survive. Selective effects of mortality and protective effects of socioeconomic resources explain the heterogeneity in ADL and its changes over time.